Empirical Study of Islamic Banks versus Conventional Banks of GCC (Global Journal of Management and Business Research, 2012)
Numerous precious researches that have been conducted at professional and academia level have established Islamic banking to be superior and a viable manner of banking in terms of profitability and stability. The objective of the study would be to analyze the performance of Islamic banks and conventional banks during the crisis and after the crisis. The study will further focus on finding the steps that have been taken by the banks so as to reduce the effects of crisis. The study will be examined by comparing the performance of Islamic and conventional banks based in the Gulf Cooperation Council (GCC) during the period of 2008 #x2013; 2011 by deploying the CAMEL testing factors. A sample of 17 Islamic banks and 10 conventional banks were selected to study the objective. Using the 2 tailed t test, our study found out that after crisis Islamic bank increased their LLR, while conventional banks increased their LLR and EQTA. During the four year period of 2008 #x2013; 2011, Islamic banks possessed adequate capital structure but have recorded lower ROAE and poor management efficiency. Asset quality and liquidity for both the modes of banking system have not recorded any significant difference.
Keywords: Islamic banks; Conventional banks; financial crisis; after crisis; CAMEL